PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI PADA MAHASISWA PROGRAM STUDI AKUNTANSI UNIVERSITAS SLAMET RIYADI SURAKARTA - Djoko Kristianto, Angga Destya Prayoga, Rispantyo & (Universitas Slamet Riyadi, 2017)
The purpose of the study: To analyze the effect of quality, career,economic,and achievement motivation on accounting student's interest to followPPAk. This research is a quantitative research with survey approach, the populationis accounting student of Slamet Riyadi University Surakarta, amounting to 96students, both regular and non regular students, the sample of accounting students ofsemester end and or have taken the course of auditing I and II at Slamet RiyadiUniversity Surakarta Amounted to 96 students. Data collection techniques usingquestionnaires with 5-point Likert scale. Data analysis technique using testinstrument research, consist of test of validity and reliability; Classical assumptiontest, consisting of multicolinearity test, heteroscedasticity, autocorrelation, andnormality; Multiple linear regression test; hypothesis testing. The results showed:Motivation of quality, career, economic, social, achievement parcial have significanteffect on accounting student interest following PPAk. motivation of quality, career,economic, social, achievement simultaneously have significant effect on accountingstudent interest following PPAk.Keywords: motivation, student interest, PPAk.